Predictors of Mid- to Long-Term Outcomes in Patients Experiencing a Knee Dislocation: A Systematic Review of Clinical Studies - Smith, John-Rudolph H.; Belk, John W.; Friedman, Jamie L.; Dragoo, Jason L.; Frank, Rachel M.; Bravman, Jonathan T.; Wolcott, Michelle L.; McCarty, Eric C. (The Journal of Knee Surgery, 2021)
Knee dislocations (KDs) are devastating injuries for patients and present complex challenges for orthopaedic surgeons. Although short-term outcomes have been studied, there are few long-term outcomes of these injuries available in the literature. The purpose of this study is to determine factors that influence mid- to long-term clinical outcomes following surgical treatment of KD. A review of the current literature was performed by searching PubMed, the Cochrane Library, and Embase to identify clinical studies published from 2010 to 2019 with a minimum 2-year follow-up that reported outcomes following surgical treatment of KDs. Ten studies (6 level III, 4 level IV) were included. At mid- (2–10 y) to long-term (>10 y) follow-up, concomitant arterial, cartilage, and combined meniscus damage were predictive factors for inferior Lysholm and International Knee Documentation Committee (IKDC) scores when compared with patients without these associated injuries. Although concomitant neurological damage may influence short-term outcomes due to decreased mobility, at longer follow-up periods it does not appear to predict worse clinical outcomes when compared with patients without concomitant neurological injury. Frank and polytrauma KDs have been associated with worse mid- to long-term outcomes when compared with transient and isolated KDs. Patients who underwent surgery within 6 weeks of trauma experienced better long-term outcomes than those who underwent surgery longer than 6 weeks after the initial injury. However, the small sample size of this study makes it difficult to make valid recommendations. Lastly, female sex, patients older than 30 years at the time of injury and a body mass index (BMI) greater than 35 kg/m2 are factors that have been associated with worse mid- to long-term Lysholm and IKDC scores. The results of this review suggest that female sex, age >30 years, BMI >35 kg/m2, concomitant cartilage damage, combined medial and lateral meniscal damage, KDs that do not spontaneously relocate, and KDs associated with polytrauma may predict worse results at mid- to long-term follow-up.
Keywords: knee dislocation; multiligament knee injury; predictors; long-term outcomes